Regional OPM breaking through the national mainstream - Laxamana, Jason Paul C. (2012)
"What is called as Original Pilipino Music or OPM in the Philippines has often been dominated by songs in the Filipino and English languages. In rare occasions during the past two decades, certain songs employing Philippine regional languages in their lyrics have broken through the playlists and hit charts of mainstream radio stations and music channels based in Metro Manila, where Filipino is the lingua franca. This thesis looked into the elements of these successful regional pop songs and what possible factors made them break through. With guidance by the Culture Overlap Model and the Post-colonial Theory of the Other, the regional songs chosen for this research underwent textual analysis. The respective genres, durations, languages, artists, and other elements of each song were drawn and analyzed to discover how they override the unintelligibility of the lyrics and manage to make the song appeal to audiences that do not comprehend the verses fully. Even though varying degrees of culture overlap are found in all of the analyzed songs, the study discovered that no single, specific formula exists that can make a regional language song succeed nationally. This paper shows, however, that there are a number of elements, or a combination of these elements, that can increase the chances of success of such songs. Some of these include: the use of popular genres like novelty, acoustic, and dance; the careful choice of words that seem similar in Filipino; and the limited use of a regional language in certain parts."